2008
DOI: 10.1007/s10126-007-9062-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of an Enzymatic Extract from Ecklonia cava on Murine Splenocytes

Abstract: We investigated whether the brown seaweed Alariaceae Ecklonia cava (E. cava) has immunological effects on splenocytes in vitro. For that purpose, we prepared an enzymatic extract from E. cava (ECK) by using the protease, Kojizyme. Here, ECK administered to ICR mice dramatically enhanced the proliferation of their splenocytes and increased the number of their lymphocytes, monocytes and granulocytes. In flow cytometry assays performed to identify in detail the specific phenotypes of these proliferating cells aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 30 publications
0
40
0
3
Order By: Relevance
“…Ecklonia cava Kjellman (class, Phaeophyceae; family, Lessoniaceae; order, Laminariales) is a brown alga used as an ingredient in food, animal feed, and fertilizers in the southwest coastal region of Japan and Korea. E. cava and polyphenols isolated from E. cava have numerous biological activities, including anti-inflammatory, anti-oxidative, anti-diabetic, and immunomodulatory (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Ecklonia cava Kjellman (class, Phaeophyceae; family, Lessoniaceae; order, Laminariales) is a brown alga used as an ingredient in food, animal feed, and fertilizers in the southwest coastal region of Japan and Korea. E. cava and polyphenols isolated from E. cava have numerous biological activities, including anti-inflammatory, anti-oxidative, anti-diabetic, and immunomodulatory (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Song et al (2011) found the significant increase of respiratory burst, myeloperoxidase and lysozyme activities in parrot fish fed a S. fusiforme containing diet and dietary supplementation of E. cava resulted in a higher lysozyme activity. Also, the results of a study by Ahn et al (2008) showed that an enzymatic extract from E. cava can enhance the proliferation of splenocytes and increase the number of lymphocytes, monocytes and granulocytes in mice. Castro et al (2004) examined the effects of eight different seaweed species on respiratory burst activity of turbot (Psetta maxima L.) phagocytes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…천연물질 및 유산균을 이용한 양계 사료첨가제 효능 및 개발 연구가 많이 이루어졌으며, 이처럼 사료첨가제 사용 시 가축의 생산성을 증진하는 데 효과가 있는 것으로 보고되었다 [9,14,17,23]. 그중 갈조류에 속하는 감태(Ecklonia cava kjellman)는 플 로르탄닌(phlorotanin), 라미나린(laminarin), 푸코이딘(fucoidin), 폴리페놀(polyphenols) 등과 같은 다당류 생리활성 물질을 다 량 함유하고 있으며 [1], 사람에서 항산화 작용뿐만 아니라 항암 및 항미생물 작용 등 기능성 소재로 증명되어 건강기 능식품으로 상용화되었다 [2,10,20]. 이와 같이 감태가 사 람에서 영양학적·면역기능학적 효능이 보고되었으나, 양계 를 포함한 가축에서 감태 연구가 많지 않은 실정이므로, 감 태의 사료첨가제로서의 효능평가는 중요한 의의를 가진다.…”
Section: 서 론unclassified